Spatial hearing and hearing aids - Akeroyd, Michael A.; Whitmer, William M. (Springer-Verlag, 2016)
The questions of whether hearing-impaired listeners are also impaired for the localization of sounds and what benefits hearing aids can provide are important for understanding the wider effects of hearing impairment. We review here 29 studies published since 1983 that have measured acuity for changes in the horizontal-plane direction of sound sources. Where possible, performance is quantified by the root-mean-square error in degrees. Overall, the results demonstrate that (1) hearing-impaired listeners have poorer left–right discrimination than normal-hearing listeners, by 5° when averaged across all experiments, although there is considerable variation across listeners and experiments; (2) hearing aids lead to a deficit of just 1°; (3) directional microphones relative to omnidirectional microphones give a deficit of 3°; (4) custom form factors have no effect relative to the behind-the-ear style; (5) acclimatization gives a benefit of 1°; (6) a unilateral fitting results in a localization deficit of 5° on average, and the deficit can reach nearly 20°; and (7) hearing-impaired listeners are particularly prone to front–back confusions; hearing aids do nothing to reduce these and sometimes increase them. Although statistically significant effects of hearing aids on localization have been reported, few of them are generalizable, as they often occurred for just some source directions, stimuli, hearing aid features, or groups of listeners. Overall, there is no experimental evidence for a benefit from hearing aids for directional acuity.